Analisis Penerapan Pendidikan Karakter Pada Mata Pelajaran IPS Di SMPN 18 Kota Bengkulu - Sazili Sazili; Herwan MDK; Sitriani Sitriani (Universitas Dehasen Bengkulu, 2024)
Character education plays an important role in forming a moral and ethical generation. Without character education, students may have difficulty distinguishing between good and bad. Character education teaches values ​​that are important for students' personal lives. This research aims to determine the application of character education in class VIII social studies subjects at SMPN 18 Bengkulu City. The research method used is qualitative research with research subjects involving social studies teachers and class VIII students. With data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. Data collection techniques use observation, interviews and documentation. The results of the research show that SMPN 18 Bengkulu City in the social studies learning process has implemented character education in the form of religious character, discipline, curiosity, responsibility and tolerance. The school also tries to continue to do its best to implement all existing character education for their students. The conclusion from this research is that SMPN 18 Bengkulu City has implemented character education in social studies subjects which can be a basis for teachers to develop their knowledge in order to create a conducive learning environment as an effort to develop student character.